2020
DOI: 10.32539/bsm.v5i1.156
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Of Patient With Foreign Body Ingestion In Palembang

Abstract: Abstract Introduction. Foreign body ingestion is a common diagnosis that presents in emergency departments—coins as the oesophagal foreign body most commonly found in infants and children. Coins retained in the oesophagus require intervention to prevent complications. This study aimed to determine oesophagal coin foreign body patient's characteristic at Mohammad Hoesin General Hospital Palembang. Method. This study design was retrospective descriptive. Samples were all patient diagnosed with oesoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…As assumed, most children were around 1-5 years old, and a mean or median of 4 years was most frequently reported, as in the present study, because they are unable to predict the risks of swallowing such things [2,5,9,12,13]. The variations in age group and others may be explained by sample selection, as some studies included only toddlers, while others included respiratory inhalation in older patients.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…As assumed, most children were around 1-5 years old, and a mean or median of 4 years was most frequently reported, as in the present study, because they are unable to predict the risks of swallowing such things [2,5,9,12,13]. The variations in age group and others may be explained by sample selection, as some studies included only toddlers, while others included respiratory inhalation in older patients.…”
Section: Discussionmentioning
confidence: 63%
“…In this study, 54 patients were included, and there was no significant gender predominance. This is true for most published articles; male patients were slightly more common, at 5-10%, than female patients [2,5,[9][10][11]. One study involving 1000 cases found male predomi-nance among toddlers compared to younger infants or older children [12].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations